Intertwinors on Functions over the Product of Spheres - Hong, D. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
We give explicit formulas for the intertwinors on the scalar functions over the product of spheres with the natural pseudo-Riemannian product metric using the spectrum generating technique. As a consequence, this provides another proof of the even order conformally invariant differential operator formulas obtained earlier by T. Branson and the present author.